ANALYSIS OF MONETARY INDICATORS DURING THE COVID-19 PANDEMY IN CIVITAL COUNTRIES (China, Indonesia, Vietnam, India, Thailand) - Asengbaramae, Rowiyah; Fikri, Rahul Ardian (International Proceeding of Law and Economic, 2020)
Inflation has become a major problem in the economy. The Indonesian government often uses a tight money policy by raising interest rates. Therefore, the interest rate becomes important, because it can be used to analyze inflation expectations. This study aims to analyze the contribution of variables from the interaction of monetary variables with macroeconomics. Where is the monetary policy variable (inflation, exchange rate, money supply, and interest rate). Then macroeconomics (GDP). This study uses secondary data or time series, namely from 2008 to 2020. The data analysis model in this study is the Simultaneous model, and the ARDL Panel. Simultaneous analysis results show that the exchange rate variable is significant to inflation, while the money supply and interest rate variables are not significant to inflation. The inflation variable has a significant effect on the exchange rate while the GDP variable has no significant effect on the exchange rate. Then the results of the ARDL Panel show that only Indonesia and Thailand are able to become leading indicators for the stability of the inflation rate, this is because all the variables or indicators in the study (exchange rate, GDP, money supply, interest rates) have a significant effect. against inflation. Suggestions in this study, namely to reduce or maintain the inflation rate so that it is at the level set by Bank Indonesia, it is better if Bank Indonesia, as the holder of the highest authority in monetary policy, must keep the BI rate at the right level in accordance with the level of inflation that occurs, so that the money supply in the community is maintained and does not cause inflation. And for the government, namely Bank Indonesia, to suppress the rate of inflation in implementing domestic monetary policy.